Reformasie as herstel van die ware diens van God: enkele aanwysers by Calvyn en Zwingli - L.F. Schulze (Koers : Bulletin for Christian Scholarship, 1998)
Reformation as restoration of the true service of God - some indicators in the work of Calvin and Zwingli